Transportation Agency Innovations in Maintenance and Development of Public Street Lighting (PJU) Tools in Sidoarjo Regency - Sukmana, Hendra; Kriya Almanfaluti, Istian; Supardi; Masrucha, Adinda Nur (Research Parks Publishers, 2021)
Public Street Lighting or commonly referred to as PJU is one of the services organized by the Regional Government that aims for the public interest and is used in lighting the streets at night, generally street lighting is located on the right or left side of the road including poles, lights, and electric cables. therefore lighting is very important in security and comfort for road users for the smooth running of users in the economic movement of an area. The purpose of this study was to determine the innovation of the Sidoarjo Regency Transportation Office in the Management and Development of Public Street Lighting (PJU) in Sidoarjo Regency. the research method used in this field survey is a qualitative method with a descriptive approach. the location of this research is at the Sidoarjo Regency Transportation Office. This research focuses on analyzing the innovation of the Sidoarjo Regency Transportation Agency in the Maintenance and Development of Public Street Lighting (PJU) in Sidoarjo Regency. this research uses 2 (two) types of data, namely secondary data and primary data. the data collection technique used in writing this article is to conduct direct observation of the field location, namely interviews, documentation, and observation. as well as informant determination techniques using purposive sampling techniques. The theory used is the theory of innovation in the public sector from Everett M. Rogers (2003), which produces several indicators, namely the Relative Advantages indicator and the Compatibility indicator. The research results on the Relative Advantages indicator explained that structurally, the organizational logic built by the Ministry of Home Affairs is that the PJU management policy in the Region is managed by the Local Government Transportation Office. In the Compatibility indicator, it is explained that the PJU management by Sidoarjo Regency Government is a portrait of the misconnection between policy innovation and organizational policy.